92 An audit of current guidelines and recommendations for mouth care in palliative and end of life care. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Daly, Laura; Allen, Yasmin; Basra, Ashvir; Sowerbutts, Jackie; Doshi, Mili; Shah, Samit
Abstract : Background: Oral complications in palliative care patients are very common. Guidelines for oral care of these patients are available from several different sources within the UK. However, these guidelines are often inconsistent and it is unclear whether the recommendations are implemented in practice. This project aims to determine if the guidelines for oral care translate into the care provided to patients, and identify any additional techniques that are not published but provide benefits to patients in end of life care. Methods: A literature review of the guidelines and published evidence was conducted to collate a list of recommendations. A pilot survey and qualitative research was conducted with Special Care Dentistry Consultants, Palliative Care consultants, geriatricians, and those providing day-to-day care for palliative care patients. This focused on what treatment was being provided to maintain oral care and comfort for palliative care patients. Results: Data was collected from a large range of health professionals working with palliative care patients. It was found that approximately 34% of respondents were not aware of any oral care guidelines for palliative care patients. Those that did were mostly aware of the NICE guidelines. There was variation between all respondents as to what treatment was routinely given for various oral conditions. Some practices restricted in certain trusts were shown to be used elsewhere, for example foam swab use (70%), which is not routinely recommended by dental professionals. Although the majority of respondents reported their patients have personalised oral care plans in place, 43% do not. Conclusions: Clearer and more concise guidelines for oral care in palliative care patients is needed to ensure staff are able to offer the same level of evidence-based care consistently across the UK. The importance of oral care plans for these patients should be promoted, to ensure patients have continuity of care.